Time series analysis of earthquake data in Peru 2017-2018 - Risco Franco, Carlos (2018)
The objective of this work is to characterize and look for behavior patterns, in areas with earthquake clusters, through the use of time series and the data of the earthquakes that occurred in Peru in 2017 and 2018.In this exploratory work, we have first used Cluster Analysis to form groups or geographic areas with near earthquake occurrence. Then we have found that the magnitude of the earthquakes in time, evaluated by geographical proximity zones, would be correlated with the magnitude of the previous earthquake, hence it was appropriate to use the ARIMA model (1,1,0), in which It is considered a lag and a difference to eliminate the presence of some trend, without the presence of moving average. We have identified eight geographical areas, in which the earthquakes are grouped. Among other results we have found that in the Arequipa-Tacna and Lima-Ica areas, the magnitudes of the earthquakes in relation to the arrival time, conform to an ARIMA model (1,1,0). On the other hand, we have also found that in the Arequipa-Tacna area, the depth of the earthquakes in relation to the time of arrival, also fits an ARIMA model (1,1,0). We have used data from the Geophysical Institute of Peru, in particular, time, latitude, altitude, magnitude, depth, among others, the same that can be found on its website of the institution.